Environmental effects of trade openness, financial development and air pollution on health outcomes in developing countries - Ahmad, Nor Asma (2021)
The rapid economic growth across developing countries has raised concerns about possible detrimental effects on the environment as the larger material and energy inputs are required for the greater economic activities. In view of these, this thesis aims to contribute to the literature on the environmental effects of trade openness, effects of financial development on environmental quality, and finally on the effects of air pollution on the health outcomes across the developing countries. The study relies on the System-Generalized Method of Moment (GMM) estimation technique for the analysis. In the first objective, the estimation models were estimated using data from 59 developing countries between the period of 2010 to 2017. From the analyses, the environmental effects of trade openness were significantly positive, where openness to trade appears to increase PM2.5 levels and CO2 emissions. The findings also suggest that across the PM2.5 estimation models, the estimated coefficients on the interactive term of trade openness with income per capita were significant, implying that higher income has the capacity to reduce environmental pollution caused by trade. In the second objective, the data covered 46 developing countries for the period of 2010 to 2017. The estimation results suggest that a country with higher domestic credit to the private sector to GDP may contribute positively to environmental quality in a country. The relationship between research and development expenditure and financial development was significantly positive, indicating that research and development expenditure was vital in enhancing environmental quality. Furthermore, improvements in environmental quality can be strengthened by the positive effects of foreign direct investment (FDI) and the inclusion of financial development in the same model. The third objective analysis establishes a significant negative effect of air pollution on health outcomes across the sample countries. The estimation of models for this objective was performed using data from 72 developing countries between the period of 2010 to 2017. Apart from that, the unfavourable effects of air pollution (PM2.5) on health outcomes were significantly moderated by governance quality. Evidence from the first objective showed that greater openness of trade policy could be detrimental to the environment. This study highlights the importance of considering the indirect effects because, when estimating trade openness impact on the environment, indirect negative effects compensate for a direct positive impact. In light of this, a policy that intensifies the trade-oriented development approaches to promote growth, which will bring environmental benefits at the same time, is deemed important. Developing countries should consider limiting emissions while maintaining economic growth prospects by investing more in green technologies, particularly manufacturing. Empirical evidence for the second objective endorses the policymakers to regulate policy that implements green values within the financial sectors via pertaining selective credit controls, such as a strategy that gives favoured treatments to the businesses that embrace low-emission production norms, which can contribute to environmental sustainability. On the other hand, a policy that assists firms in integrating sustainability by conducting research and development in upgrading available technologies and lowering financial barriers to technology availability is essential. The findings also suggest that policies aimed at improving the financial system will make financing more accessible to foreign businesses and investors, allowing them to start on capital projects at a lower cost. Empirical findings of the third objective emphasise the need for health authorities considering the significant health burden, as well as the need for environmental and health ministries to collaborate to address this issue. Ministries of the environment should implement clear, effective, and credible policies to reduce air pollution. Health authorities can raise public awareness on environmental issues by educating the public about the health benefits of clean air, as well as a partnership with a variety of public and private institutions. As the developing countries pursue an acceptable balance between economic development and environmental quality, growth policies need to integrate effective strategies to protect the country's health population into policymaking.